2017
DOI: 10.1007/s10484-017-9364-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart Rate Variability Biofeedback on Sport Performance, a Systematic Review

Abstract: Aim is to determine if the training with heart rate variability biofeedback allows to improve performance in athletes of different disciplines. Methods such as database search on Web of Science, SpringerLink, EBSCO Academic Search Complete, SPORTDiscus, Pubmed/Medline, and PROQUEST Academic Research Library, as well as manual reference registration. The eligibility criteria were: (a) published scientific articles; (b) experimental studies, quasi-experimental, or case reports; (c) use of HRV BFB as main treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 40 publications
0
76
0
5
Order By: Relevance
“…Another advantage of measuring the HRV coherence ratio is that it likely serves as an indicator of the cardiorespiratory coupling (cardiorespiratory phase synchronization) that occurs during deep sleep and may help facilitate homeostasis between the ANS and cardiopulmonary systems (Tobaldini et al 2013 ; Cabiddu et al 2012 ; Penzel et al 2016 ; Jerath et al 2014 ; Garcia et al 2013 ). Because HRV coherence can be achieved via behavioral interventions that implement a resonant frequency breathing protocol (i.e., HRV biofeedback) (Lehrer et al 2000 ; Garcia et al 2013 ; Wheat and Larkin 2010 ; Lehrer and Gevirtz 2014 ), the authors speculate that, if the findings of the current study are confirmed, HRV biofeedback may help facilitate shift work adaptation via increases in HRV coherence, which have been associated with improvements in cognitive performance and sleep, as well as reductions in stress, anxiety, and depression (Goessl et al 2017 ; Thayer et al 2009 ; Lehrer 2018 ; Lehrer and Gevirtz 2014 ; Morgan and Mora 2017 ; Sakakibara et al 2013 ), and are all conditions that are commonly encountered among shift workers.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Another advantage of measuring the HRV coherence ratio is that it likely serves as an indicator of the cardiorespiratory coupling (cardiorespiratory phase synchronization) that occurs during deep sleep and may help facilitate homeostasis between the ANS and cardiopulmonary systems (Tobaldini et al 2013 ; Cabiddu et al 2012 ; Penzel et al 2016 ; Jerath et al 2014 ; Garcia et al 2013 ). Because HRV coherence can be achieved via behavioral interventions that implement a resonant frequency breathing protocol (i.e., HRV biofeedback) (Lehrer et al 2000 ; Garcia et al 2013 ; Wheat and Larkin 2010 ; Lehrer and Gevirtz 2014 ), the authors speculate that, if the findings of the current study are confirmed, HRV biofeedback may help facilitate shift work adaptation via increases in HRV coherence, which have been associated with improvements in cognitive performance and sleep, as well as reductions in stress, anxiety, and depression (Goessl et al 2017 ; Thayer et al 2009 ; Lehrer 2018 ; Lehrer and Gevirtz 2014 ; Morgan and Mora 2017 ; Sakakibara et al 2013 ), and are all conditions that are commonly encountered among shift workers.…”
Section: Discussionmentioning
confidence: 56%
“…HRV coherence can be achieved by practicing a paced breathing exercise (resonant frequency breathing) using a procedure known as HRV biofeedback (Wheat and Larkin 2010 ; Gevirtz 2013 ; Lehrer et al 2000 ; Lehrer and Gevirtz 2014 ). Results from interventions targeting HRV coherence suggest that it may alleviate adverse impacts encountered among shift workers by facilitating improvements in cognitive performance and sleep, and by reducing stress, anxiety, and depression (Goessl et al 2017 ; Thayer et al 2009 ; Lehrer 2018 ; Lehrer and Gevirtz 2014 ; Morgan and Mora 2017 ; Sakakibara et al 2013 ). Additionally, the restorative properties of deep sleep are considered to be related to the parasympathetic dominance, resonant frequency breathing, and cardiorespiratory coupling that occur during non-rapid eye movement (NREM) and slow-wave sleep (Tobaldini et al 2013 ; Cabiddu et al 2012 ; Penzel et al 2016 ; Jerath et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we consider that simplicity of monitoring and its interpretation are essential to encourage usage of HRV measurement as a valid tool in sports practice. HRV recording is relatively straightforward because numerous free applications have been developed for regular smartphones [4]. In addition, although the recorded HRV data could be available almost instantaneously to the coach or other staff of the sports team for inspection, analysis, and feedback, the interpretation of HRV and its changes is not simple because response magnitude and timing are individually determined by multiple factors including biological variation, emotions, and training context [2,27,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…One marker of the functional status of an organism, that gives an indication of the balance between the sympathetic and parasympathetic nervous system, is heart rate variability (HRV). This indicator has recently become quite popular and has been associated with numerous conditions ranging from sleep quality to sports performance [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation